The laziness of the critic (XXI Century. Spanish Literature and Culture, 2007)
The novel is the reflection of society: of its entirety, of its changes and most ofall of its present, and it is the work of the critic to draw all of this from the text inorder to distinguish what is (obviously within the fiction) fiction and what is not.Using history as a base doesn´t assume the writing of a historical novel since allnovels end up being historical and in all novels appears the present of the author.What distinguishes some novels from others is the way the story is told of itscharacters (always a mirror of the desires of the reader) and from what point of viewthis is done.
Keywords: novel; society; critic